Effect of Immunomodulators and Antibiotic on Haematological Profile of Gir Cows with Subclinical Endometritis - Parikh, Suryakant S.; Kavani, Fulabhai S.; Savsani, Harish H.; Vasava, Amrita A.; Savaliya, Bhagvanji D. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study was aimed to assess the influence of immunomodulators and antibiotic on haematological profile in subclinical  endometritis (SCE) affected Gir cows. Forty-eight apparently healthy Gir cows at 40-60 days postpartum, 4 to 8 years old, were randomly  selected from an organized dairy farm. All the postpartum cows with (n=40) or without (n=8) subclinical endometritis were screened  using cytobrush technique. Subclinical endometritis affected cows were randomly divided into 5 groups (8 animals/group). In Group A,  Escherichia coli LPS (100 µg in 30 mL PBS once i/u), in Group B, oyster glycogen (500 mg in 30 mL PBS once i/u), in Group C, levofloxacin  (30 mL for three consecutive days i/u), in Group D, garlic extract (5 mL in 30 mL distilled water for three consecutive days i/u) was used,  while Group E (positive control) did not receive any treatment and was allowed for self-cure. A group of normal healthy cows (n=8)  served as negative control (Group F). Blood samples were collected at estrus before treatment (0 h) and after treatment (72 h and at  subsequent estrus) and compared for changes in haematological parameters. The results revealed significantly (P
Keywords: Gir cows; Haematological profile; Subclinical endometritis; Therapeutic regimens